IDENTIFIKASI GULMA TANAMAN PADI (Oryza sativa L. var. Ciherang) SUMATARA SELATAN - Syarifah Syarifah; Ike Apriani; Ra Hoetary Tirta Amallia (LP4MK STKIP PGRI Lubuklinggau, 2018)
The growth of weeds in the rice fields can reduce production. Weed is a disrupting plant that grows and spreads rapidly so it becomes a nutritional competitor for cultivated plants. This study aims to identify rice weeds in the fields of Rimau District, Banyuasin, South Sumatra. The research method used was descriptive method with purposive sampling on wetland rice fields of the Ciherang variety. Sampling was carried out in a critical period (3-6 weeks after planting) in rice fields. The results of weed identification obtained 6 families consisting of 15 species, namely Ageratum conyzoides L., Crassocephalum crepidioides, Cleome rutidisprema DC., Cyperusroduntus L. Cyperus compressus, Eleocharis palustris L., Frimbristylis miliacea L. Vahl, Phylanthus naruri L., Eurphobia hirta, Cynodon dactylon (L.) Press., Digitaria ciliaris (Retz.) Koel., Echinochola colona (L.) Link., Eleusinindica (L.) Gaertn., Paspalum scrobiculatum L., Ludwigia octovalvis (Jacq.) Raven. The Poaceae family is most commonly found as a rice weed in Rimau District, South Sumatra.